Kepuasan Belajar Mahasiswa Keperawatan Terhadap Implementasi Flipped Classroom - Larissa Oktavia Syafri; Totok Harjanto; Ariani Arista Putri Pertiwi (PSIK FKKMK UGM, 2020)
Background: Nursing students are experiencing difficulties in understanding the material during clinical skills learning due to differences in content delivery among instructors. One possible solution is to implement the flipped classroom method, which can provide a more interactive learning approach. It is hoped that the implementation of this method will increase the level of student satisfaction in learning nursing skills. Objective: To assess the satisfaction of nursing students regarding the implementation of flipped classroom in clinical skills learning in nursing. Method: This study was quantitative descriptive research using a cross-sectional research design. 102 respondents of nursing students at Gadjah Mada University (UGM) of the first semester at the 2019/2020 academic year were selected using total sampling. The instrument used was the Collaborative Learning, Social Presence, and Satisfaction (CLSS) questionnaire. The data were analyzed using univariate analysis to describe the characteristics of the respondents and the variables under investigation. Outcome: The satisfaction level of respondents regarding the implementation of the flipped classroom method was categorized as high, moderate, and low, with percentages of 42,2%, 56,9%, and 0,9%, respectively. Conclusion: The level of satisfaction among nursing students at UGM regarding the implementation of the flipped classroom method was at the moderate range.ABSTRAKLatar belakang: Mahasiswa keperawatan mengalami kesulitan dalam memahami materi saat pembelajaran keterampilan klinis karena perbedaan penyampaian materi antar instruktur. Salah satu solusi yang dapat dilakukan adalah dengan menggunakan metode flipped classroom, yang dapat memberikan pendekatan pembelajaran yang lebih interaktif. Diharapkan tingkat kepuasan pembelajaran mahasiswa keperawatan dapat meningkat dengan adanya metode ini. Tujuan: Untuk mengetahui gambaran kepuasan belajar mahasiswa keperawatan terhadap implementasi flipped classroom dalam pembelajaran keterampilan klinik keparawatan. Metode: Penelitian deskriptif kuantitatif dengan desain penelitian cross sectional. Teknik pengambilan responden menggunakan total sampling dengan sampel sebanyak 102 mahasiswa keperawatan di Universitas Gadjah Mada (UGM) semester satu tahun ajaran 2019/2020. Instrumen yang digunakan adalah the collaborative learning, social presence, and satisfaction (CLSS) questionnaire. Analisis data yang dilakukan menggunakan analisis univariat untuk mendeskripsikan karakteristik responden dan variabel yang diteliti. Hasil: Tingkat kepuasan responden terhadap implementasi flipped classroom berada pada kategori tinggi, sedang, dan rendah dengan persentase sebesar 42,2%, 56,9%, dan 0,9%. Kesimpulan: Tingkat kepuasan mahasiswa keperawatan di UGM terhadap implementasi flipped classroom berada dalam rentang sedang.